2012
DOI: 10.1111/ggi.12008
|View full text |Cite
|
Sign up to set email alerts
|

Positive affect as a predictor of lower risk of functional decline in community‐dwelling elderly in Japan

Abstract: Positive psychological well-being, specifically the feeling of satisfaction with life, happiness and energy, might have a favorable effect on the maintenance of functional ability, regardless of negative affect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 37 publications
0
31
3
3
Order By: Relevance
“…These findings are in contrast to previous research from Japan 11) , which could be related to cultural differences 30) . Koreans tend to experience difficulty in expressing positive emotions, unlike individuals in other countries; this may be a consequence of Confucian ethics 31) .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings are in contrast to previous research from Japan 11) , which could be related to cultural differences 30) . Koreans tend to experience difficulty in expressing positive emotions, unlike individuals in other countries; this may be a consequence of Confucian ethics 31) .…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, emotional conditions, including depression, might play an important role in functional decline 11) . However, most studies focused on the relationship between symptoms of depression and functional decline were cross-sectional and thus could not ascertain causal relationships [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the study result in which researchers demonstrated the independent association of positive affect in lowering the risk of functional decline. [17] Several explanations have been proposed for the mechanisms underlying the link between positive affect and cognitive health. For example, favorable health behaviors such as not smoking are more prevalent among happier people.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have used GDS in this manner to assess the predictive power of positive affect on older person's health, such as functional decline or cognitive impairment. [17,23] The five GDS items for measuring positive affect are "feeling satisfied with life," "feeling happy most of the time," "feeling full of energy," "feeling wonderful to be alive," and "being in good spirits most of the time." The answer was dichotomized as yes/no.…”
Section: Explanatory Variablementioning
confidence: 99%
See 1 more Smart Citation